2014
DOI: 10.4314/sajas.v43i5.14
|View full text |Cite
|
Sign up to set email alerts
|

Dietary energy level for optimum productivity and carcass characteristics of indigenous Venda chickens raised in closed confinement

Abstract: A study was conducted to determine dietary energy levels for optimum productivity and carcass characteristics of indigenous Venda chickens raised in closed confinement. Four dietary treatments were considered in the first phase (1 to 7 weeks) on two hundred day-old unsexed indigenous Venda chicks indicated as EVS 1 , EVS 2 , EVS 3 and EVS 4 (11, 12, 13 and 14 MJ ME/kg DM, respectively) and each treatment was replicated five times. In the second phase (8 -13 weeks), 160 indigenous Venda female chickens, aged ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…An advantage of this high proportion of household waste is that the birds' owners can add supplements through this portion of the diet if deficiencies are identified. Alabi et al (2013) reported that diets containing 12.34 MJ ME/kg DM to 12.91 MJ ME/kg DM supported optimal feed intake, growth rate and feed conversion ratios during the starter and grower phase of Venda chicks under well-controlled management conditions. In the present study the high AME of 12.7 MJ/kg DM to 13.5 MJ/kg DM of crop contents suggests that the fowls had access to diets that were high in energy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An advantage of this high proportion of household waste is that the birds' owners can add supplements through this portion of the diet if deficiencies are identified. Alabi et al (2013) reported that diets containing 12.34 MJ ME/kg DM to 12.91 MJ ME/kg DM supported optimal feed intake, growth rate and feed conversion ratios during the starter and grower phase of Venda chicks under well-controlled management conditions. In the present study the high AME of 12.7 MJ/kg DM to 13.5 MJ/kg DM of crop contents suggests that the fowls had access to diets that were high in energy.…”
Section: Discussionmentioning
confidence: 99%
“…In recent studies, the growth potential of the Venda chicken (Norris et al, 2007), and its protein (Mbajiorgu et al, 2011) and metabolizable energy (Alabi et al, 2013) requirements have been investigated under confined optimal management conditions. However, traditional scavenging systems are low input methods in which the production of the animal is usually adjusted to feed availability, implying that the producer has to rely on what is locally and seasonally obtainable (Schiere & De Wit, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Metabolizable energy (ME), a macronutrient composition of diet, is a pivotal factor that influences the feed efficiency, growth performance, and carcass composition of poultry (9,10). Many recent studies have addressed human and animal food preferences under stress conditions (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been conducted to improve the productivity of local chickens through efficient feeding (Table 3). According to Alabi [84], protein, lysine (a base for all other amino acids) and energy requirements of local chickens must be met optimally in order to improve and maximise productivity. According to Kingori et al [36], a protein level of 16% in local chickens aged between 14 and 21 weeks has been observed to optimise feed intake and growth.…”
Section: Enhancement Of the Performance Of Local Chickens Through Nut...mentioning
confidence: 99%
“…Mbajiorgu [86] reported that indigenous chickens aged between one and six weeks old require a diet containing an energy level of 14 MJ ME per kg Dry Matter (DM) for optimal growth. According to Alabi et al [84], a diet containing 12.34 MJ ME/kg DM to 12.91 MJ ME/kg DM is recommended for optimal growth performance during the starter and grower phase of Venda chicks under well-controlled management conditions.…”
Section: Enhancement Of the Performance Of Local Chickens Through Nut...mentioning
confidence: 99%